Physicochemical and antibiofilm properties of new ready-to-use and powder/gel bioceramic endodontic sealers - Jéssica Arielli PRADELLI; José Leandro de Abreu JAMPANI; Airton Oliveira SANTOS-JUNIOR; Mario TANOMARU-FILHO; Juliane Maria GUERREIRO-TANOMARU (Brazilian Oral Research)
Abstract NeoSealer Flo (NSF) is a novel ready-to-use endodontic bioceramic sealer, and NeoMTA2 (NMTA2) is a powder-gel bioceramic used as a repair or filling material. Setting time (ST), pH, solubility, radiopacity, and flow were evaluated in accordance with the ISO 6876:2012 standards for NSF and NMTA2, in comparison with Bio-C Sealer (BCS) and AH Plus Jet (AHP). Bond strength was assessed using the push-out test. Antibiofilm activity was evaluated by a modified direct contact test on Enterococcus faecalis biofilm with fresh sealer eluate and material after setting. Data were analyzed using the t-test, ANOVA, and Tukey post-hoc tests (α = 0.05). AHP exhibited the highest ST value, followed by NMTA2 (p < 0.05). NSF and BCS showed solubility above 3%, while NMTA2 exhibited values lower than 3% (p < 0.05). All materials demonstrated radiopacity above 3 mm Al (p > 0.05). NMTA2 demonstrated flow below ISO-recommendation (p < 0.05). NSF showed the highest bond strength values (p < 0.05). The bioceramic sealers induced higher pH compared with AHP (p < 0.05). NMTA2 exhibited more significant antibiofilm activity after the sealer set (p < 0.05). For fresh sealer eluate, NSF, BCS, and AHP demonstrated higher levels of antibiofilm activity compared with NMTA2 (p < 0.05). NSF and NMTA2 demonstrated the required physicochemical and mechanical properties, as well as antibiofilm activity against E. faecalis. However, NSF and BCS presented higher solubility. NMTA2 presented adequate solubility, however lower flow rates than those recommended by ISO standards.